2020
DOI: 10.1159/000510120
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Significance of Charcot-Leyden Crystal Protein in Nasal Secretions in Recurrent Chronic Rhinosinusitis with Nasal Polyps

Abstract: <b><i>Introduction:</i></b> The recurrence occurs frequently among patients with chronic rhinosinusitis with nasal polyps (CRSwNP), and predictors that could be conveniently detected during practice in outpatient service are needed. <b><i>Objective:</i></b> We aimed to illustrate that the concentration of Charcot-Leyden crystal (CLC) in nasal secretions can effectively and noninvasively predict polyp recurrence. <b><i>Methods:</i></b> 108 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 63 publications
0
24
0
Order By: Relevance
“…The detailed parameters of ROC analysis are displayed in Table 5 . Based on the optimal cutoff values of the serum MIF level obtained by ROC analysis, patients were categorized into low MIF level group (serum MIF level <22.5 ng/ml, n = 51) and high MIF level group (serum MIF level >22.5 ng/ml, n = 29) as similarly described in previous publications ( Liang et al, 2020 ; Wu et al, 2021 ). In low MIF level group, the good-response rate was 78.4%, which was higher than that in high MIF level group (17.2%, p < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…The detailed parameters of ROC analysis are displayed in Table 5 . Based on the optimal cutoff values of the serum MIF level obtained by ROC analysis, patients were categorized into low MIF level group (serum MIF level <22.5 ng/ml, n = 51) and high MIF level group (serum MIF level >22.5 ng/ml, n = 29) as similarly described in previous publications ( Liang et al, 2020 ; Wu et al, 2021 ). In low MIF level group, the good-response rate was 78.4%, which was higher than that in high MIF level group (17.2%, p < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…As EETosis has been evident in various allergic diseases including ECRS [ 15 ], the released galectin-10 levels in serum might reflect the activity of eosinophil-related diseases. Although the levels of galectin-10 have been assessed in the tissues from patients with eosinophilic esophagitis [ 15 ], or nasal secretion during nonallergic rhinitis of patients with eosinophilia syndrome [ 16 ], aspirin-sensitive respiratory disease [ 17 ], and chronic rhinosinusitis (CRS) with nasal polyps [ 18 ], the clinical relevance of serum galectin-10 is totally unknown to date. In this study, the rapid decrease in serum galection-10 after mepolizumab treatment suggested the resolutions of CLC-mediated inflammation by mepolizumab, warranting further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding indicates the usefulness of serum ECP over blood eosinophil count as potential predictive factor of mepolizumab efficacy for ECRS in severe asthma. Galectin-10 in nasal secretion has been shown to be significantly higher in patients with recurrent nasal polyp [ 18 ], suggesting an important role of galectin-10 in formation of nasal polyp. However, the clinical relevance of serum galectin-10 in nasal polyp or ECRS has not been reported yet.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that individuals with higher levels of Charcot-Leyden proteins and mRNA in sinonasal tissues are associated with having eosinophilic CRS and disease recurrence. [23][24][25] The negative effects of airborne pollutants on respiratory health have been widely reported in epidemiological and experimental studies. There is only limited literature on the effects of pollution in patients with CRS.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that individuals with higher levels of Charcot-Leyden proteins and mRNA in sinonasal tissues are associated with having eosinophilic CRS and disease recurrence. 2325…”
Section: Discussionmentioning
confidence: 99%